Airway pressure release ventilation as a recruitment maneuver in mechanically ventilated children with restrictive lung disease - Alqahtani, Mashael F.; Allen, Jessica E.; Johnson, Craig M.; Maul, Timothy M.; Koshel, Christine K. (Frontiers in Pediatrics, 2025)
RationaleRestrictive lung disease is common in pediatric patients, leading to acute-on-chronic respiratory failure and the need for invasive mechanical ventilation. There is no consensus on lung recruitment maneuvers.ObjectivesTo examine the use of airway pressure release ventilation (APRV) in patients with restrictive lung disease as an effective open-lung tool maneuver.MethodsThis single-center retrospective case series included patients with restrictive lung disease in a 28-bed pediatric intensive care unit from 2013 to 2024, who developed acute-on-chronic respiratory failure requiring invasive mechanical ventilation. Inclusion criteria were ventilation for at least 48 h, with at least 24 h in APRV. Descriptive statistics were performed.Measurements and main results18 patient encounters met inclusion criteria. Subjects were divided into two groups: neuromuscular disease (14 encounters) and truncal obesity (4 encounters). Lung surface area improved significantly in the first 12–24 h of APRV use: neuromuscular group by 7,600 mm2 [95% CI, 4,000–11,000 mm2]; p < 0.001, and obesity group by 15,000 mm2 [95% CI, 3,000–27,000]; p = 0.018. Atelectasis improved at 12–24 h and 48 h from starting APRV, with mean differences of 14% [95% CI, 4%–24%]; p = 0.005 and 14% [95% CI, 3%–25%]; p = 0.009, respectively. As expected, oxygenation improved substantially in both groups.ConclusionAPRV is a safe and effective method for improving atelectasis and oxygenation in children with RLD related to neuromuscular conditions and obesity. Further high-quality prospective studies are needed to establish clear guidelines for its use.